Veliki klinkač Aquila clanga na Ljubljanskem barju - Trebušak, Marko (Acrocephalus, 1999)
Between November 5th and 12th 1998, two juvenile Spotted Eagles Aquila clanga were observed at Ljubljansko barje (Ljubljana Marshes) between the villages ofBevke and Podpeč. This is the eighth record of this particular bird of prey in Slovenia and the first observation of two individuals at the very same time. The occurrence coincided with the autumn rains and floods that killed numerous small mammals, on which eventually fed these birds.
Keywords: bird; Birds; ptice; ornitologija; Ecosystem; Slovenia; Slovenija; Ljubljana Marshes; Ljubljansko barje